Qualified Digital Ecosystems As an Academic Information System Framework in The Industrial 4.0 - Ino Sulistiani; Nursaeni; Bobur Sobirov (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
Leveraging quality models to establish a robust digital ecosystem is imperative in the Industry 4.0 era. Existing Academic Information System (AIS) software often lacks comprehensive adoption of quality models as core system instruments. As a critical component of the education sector's digital transformation, AIS represents a vital ecosystem for facilitating efficiency and innovation in this industrial era. This study addresses these gaps by implementing a comprehensive quality framework for AIS, integrating cloud computing for enhanced security and privacy, and employing the Web-Based Application Quality Model (WBAQM) as the primary development framework. The research also utilizes ISO 9126 and ISO/IEC 25010 quality models to establish usability and security standards, while the Academic Information System Quality Instrument (AISQI) is introduced to evaluate system performance. Additionally, the COBIT framework is applied to audit and enhance AIS functionality, ensuring alignment with academic and operational needs. The findings demonstrate that adopting quality models significantly improves the reliability, usability, and security of AIS software, delivering a system that aligns with both functional requirements and user expectations. This research contributes to the digital transformation of educational institutions in Indonesia by providing a scalable and efficient AIS framework. By aligning with Industry 4.0 principles, the proposed model ensures quality assurance and fosters innovation, enabling educational institutions to adapt to evolving technological demands and improve overall institutional performance.